Pengaruh Kepemilikan Asing Terhadap Nilai Perusahaan Dan Dividen - Hizazi, Achmad (Ilmiah Manajemen Bisnis, 2014)
ABSTRACTThis research investigates whether foreign ownerships are associated with Firms Value and Dividend Policy. Research was conducted on 99 manufacture Firms that are listed in Bursa Efek Indonesia (Jakarta Stock Exchange) from 2010 to 2011. Quantitative analysis were conducted by regressing TobinÃ¢â¬â¢s Q proxies firms value, Dividend Per Share and cash dividend to foreign ownerships. This research finds evidence that foreign ownership has significant effects to firmsÃ¢â¬â¢ value especially foreign ownership with majority ownership with 50% ownership or more which is robust in pool regression and fixed effect regression. While effect foreign ownerships to dividend, proxy foreign ownerships which affect dividen per share and cash dividend remain the same but significancy lesser than to firm value.Keywords: Foreign ownership, TobinÃ¢â¬â¢Q, DPS and Cash Dividen